REPRESENTASI KONFLIK KEBANGKITAN SOSIAL DALAM FILM ANIME ONE PIECE ARC DRESSROSA (STUDI ANALISIS ROLAND BARTHES) - M. Soffan Azis; Nurma Yuwita (Triwikrama: Jurnal Ilmu Sosial, 2023)
Name M. Soffan Azis, Communication Studies Program at Yudharta University Pasuruan 2023. Representation of Social Development Conflicts in the Anime One Piece Arc Dressrosa, Supervisor Nurma Yuwita, S., M.I.Kom. Movies have appeal for children to adults. The One Piece Anime film was produced in 1999 and is now available in the Bstation application. His goal is to find the world's greatest treasure, known as "One Piece", and rise in the ranks to become the Pirate King. The main topic of discussion in this thesis is Roland Barthes' Analysis of Conflict Representation of Social Awakening in Dressrosa Arc Anime One Piece Film. The purpose of this researcher is to understand the conflicts that occur in the Anime One Piece Arc Dressrosa. The research conducted here is descriptive qualitative research. Data analysis for this film uses qualitative methods based on Roland Barthes' semiotic analysis.